2017
DOI: 10.1371/journal.pone.0185581
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in neonatal sepsis: Incidence, severity and risk factors

Abstract: ObjectivesThrombocytopenia is a frequent problem in neonatal sepsis and is among the most predictive, independent risk factors for sepsis-associated mortality. This study aims to clarify the occurrence, severity and duration of thrombocytopenia in neonatal sepsis.Study designA cohort study was carried out among all neonates with proven culture positive sepsis that were admitted to a tertiary NICU between 2006 and 2015 (n = 460). The occurrence, severity and duration of thrombocytopenia were recorded, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 22 publications
13
57
1
2
Order By: Relevance
“…Furthermore, the most commonly isolated organisms in septic neonates were gram negative (E. coli and Klebsiella) in 55% of cases. These results agree well with Ree et al [17], as they found that severe NT occurred in 20% of septic neonates and the most commonly isolated organisms were gram negative. The pathogenesis of NT in neonatal sepsis is not completely understood.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the most commonly isolated organisms in septic neonates were gram negative (E. coli and Klebsiella) in 55% of cases. These results agree well with Ree et al [17], as they found that severe NT occurred in 20% of septic neonates and the most commonly isolated organisms were gram negative. The pathogenesis of NT in neonatal sepsis is not completely understood.…”
Section: Discussionsupporting
confidence: 92%
“…80% of neonates, in addition to multiple organ failure, presented a hemorrhagic syndrome, with thrombocytopenia; this is reported also in the literature [22][23][24][25] . The elevated level of C-reactive protein, as a marker of the infectious-inflammatory process of the newborn, was noted in only three children (12%) with early neonatal sepsis.…”
Section: Discussionsupporting
confidence: 55%
“…Thrombocytopenia is one of these (3). Thrombocytopenia occurs in half of the cases with proven sepsis (10) and is used as a marker for screening of neonatal sepsis. It has been reported to be more common in association with some sepsis causing germs.…”
Section: Discussionmentioning
confidence: 99%